STRATEGI TALENT INCUBATION, MICROLEARNING, DAN SOCIAL LEARNING UNTUK MENINGKATKAN WORK READINESS DAN INNOVATIVE CAPABILITY MELALUI SELF DIRECTED LEARNING - Sari Budiarti; Sriyunia Anizar (JURNAL KINDAI, 2025)
This study aims to examine the effects of Talent Incubation Strategy, Microlearning Experience, and Social Learning Support on students’ Work Readiness and Innovative Capability, with Self-Directed Learning (SDL) as a mediating variable. A quantitative approach with an explanatory survey design was employed using purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that Social Learning Support and Microlearning Experience have significant effects on SDL, while the influence of Talent Incubation Strategy is relatively weak. Furthermore, SDL has a strong effect on both Work Readiness and Innovative Capability. The R² values reveal that 55.7% of SDL variance, 41.1% of Work Readiness, and 80.4% of Innovative Capability are explained by the model. These findings highlight the critical mediating role of SDL in enhancing students’ employability and innovation capacity in digital learning environments. Keywords: talent incubation, microlearning, social learning, self directed learning, work readiness, innovative capability